Nano-Dimensional Carbon Nanosphere Supported Non-Precious Metal Oxide Composite: A Cathode Material for Sea Water Reduction - Jayasmita Jana; Tran Van Phuc; Jin Suk Chung; Won Mook Choi; Seung Hyun Hur (Nanomaterials, 2022)
Generation of hydrogen fuel at cathode during the electrolysis of seawater can be economically beneficial considering the vast availability of the electrolyte although it faces sluggishness caused by the anode reactions. In this regard a carbon nanosphere-protected CuO/Co3O4 (CCuU) composite was synthesized through heat treatment and was used as the cathode material for electrocatalytic seawater splitting. CCuU showed a significantly low overpotential of 73 mV@10 mA cm−2, Tafel slope of 58 mV dec−1 and relatively constant activity and morphology over a long time electrocatalytic study. A synergy within metal oxide centers was observed that boosted the proton-electron transfer at the active site. Moreover, the presence of carbon support increased the electroactive surface area and stability of the composite. The activity of the CCuU was studied for HER in KOH and alkaline NaCl solution to understand the activity. This work will pave the way for designing mesoporous non-precious electrocatalysts towards seawater electrocatalysis.